(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Socioeconomic status (SES) plays a very important role in individuals and influences every aspect of human life. Family income, education, employment, unemployment, occupation, family size, and locality of residence are those conditions that impact socioeconomic status to explain criminal behavior among people. Moreover, others may say that because of the excessive number of people or number of people living in a family, the cost of living at home is difficult to sustain. It also encompasses individuals with low educational attainment, low income, and unemployment. One of the solutions that we suggest is to increase the employee’s minimum wage and lower the standards or requirements of work so that more people will be employed and they can produce enough and support their needs daily to prevent them from committing a crime. The study reveals that socioeconomic status has an impact, wherein in education, the respondents are spending their time and money cutting classes more than attending classes. As to income, most of the respondents agreed they can save money/ have savings for future purposes. In employment, most of the respondents are not interested in their work; they are just working to provide financially. Also, there are socioeconomic conditions that contribute to criminal behavior, such as unemployment and the high qualifications or requirements for finding a job, which is why most of the respondents are having difficulties finding a job. For income level, the respondents can provide their daily needs finances, especially for school expenses. And lastly, regarding prevalent levels of unemployment, the responses were that they are undecided if they want to work or not. The researchers recommend an assessment guide to give information about the impact of socioeconomic status on one’s criminal behavior. This is done in collaboration with officials of Barangay Gaya-gaya and LGU for dissemination of information through flyers, brochures, seminars, and workshops. And through the use of social media platforms to help with the dissemination of information regarding the study.